2019
DOI: 10.1038/s41401-019-0303-z
|View full text |Cite
|
Sign up to set email alerts
|

Propofol affects mouse embryonic fibroblast survival and proliferation in vitro via ATG5- and calcium-dependent regulation of autophagy

Abstract: Propofol is a commonly used intravenous anesthetic agent, which has been found to affect cell survival and proliferation especially in early life. Our previous studies show that propofol-induced neurodegeneration and neurogenesis are closely associated with cell autophagy. In the present study we explored the roles of autophagy-related gene 5 (ATG5) in propofol-induced autophagy in mouse embryonic fibroblasts (MEF) in vitro. We showed that ATG5 was functionally related to propofol-induced cell survival and dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…However, clinically relevant doses of propofol can promote the proliferation of NPC cells and increase the differentiation of neurons. Similar to the findings reported Qiao et al (2017) and Xu et al (2020) demonstrated that dose-dependent propofol affects the proliferation and death of mouse fibroblasts in vitro via regulation of autophagy by affecting calcium release, and AGT5 plays an important role in this process. More importantly, the cells with Alzheimer’s disease characteristics were more susceptible to propofol neurotoxicity ( Xie et al, 2007 ).…”
Section: Introductionsupporting
confidence: 86%
“…However, clinically relevant doses of propofol can promote the proliferation of NPC cells and increase the differentiation of neurons. Similar to the findings reported Qiao et al (2017) and Xu et al (2020) demonstrated that dose-dependent propofol affects the proliferation and death of mouse fibroblasts in vitro via regulation of autophagy by affecting calcium release, and AGT5 plays an important role in this process. More importantly, the cells with Alzheimer’s disease characteristics were more susceptible to propofol neurotoxicity ( Xie et al, 2007 ).…”
Section: Introductionsupporting
confidence: 86%
“…30 In mouse embryonic fibroblasts, it was also found that propofol caused a large outflow of Ca 2+ in the endoplasmic reticulum and thus cell death. 31 Therefore, calcium overload is closely related to the neurotoxicity of propofol. These findings may provide a new way to alleviate the developmental neurotoxicity caused by propofol by correcting the dysregulation of calcium concentration.…”
Section: The Mechanism Of Propofol On Brain Damage During Developmentmentioning
confidence: 99%
“…Evidence shows that propofol can regulate the occurrence and development of tumor cells. Retrospective study shows that, compared with inhalation anesthesia, total intravenous anesthesia by propofol can improve the overall survival of patients with various types of tumors [9]. Different from inhalation anesthetics and other intravenous anesthetics, propofol can inhibit the proliferation, migration, invasion and angiogenesis of various tumor cells by acting on different cell signal pathways, and restore or enhance the sensitivity of tumor cells to chemotherapeutic drugs [10].…”
Section: Introductionmentioning
confidence: 99%